Credit Rationing, Income Exaggeration, and Adverse Selection in the Mortgage Market. (December 2016) - AMBROSE, BRENT W.; CONKLIN, JAMES; YOSHIDA, JIRO
ABSTRACT: We examine the role of borrower concerns about future credit availability in mitigating the effects of adverse selection and income misrepresentation in the mortgage market. We show that the majority of additional risk associated with "low‐doc" mortgages originated prior to the Great Recession was due to adverse selection on the part of borrowers who could verify income but chose not to. We provide novel evidence that these borrowers were more likely to inflate or exaggerate their income. Our analysis suggests that recent regulatory changes that have essentially eliminated the low‐doc loan product would result in credit rationing against self‐employed borrowers.